Optimalisasi Kemampuan Menulis Artikel Ilmiah Guru - Widowati Pusporini; Devi Septiani; Nuryani Dwi Astuti (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2021)
The problem behind the holding of these abdimas is the need to increase teachers' performance in the ability to write scientific works. The scientific work of teachers is needed for the fulfillment of one of the conditions of promotions. Abdimas aims to: provide knowledge to teachers about the rules of scientific article writing technique; provide services and assistance to teachers, how to develop articles from research reports; guide teachers in the process of submitting articles in national journals. The methods in this abdimas are of several types: video conferences, discussions, and practices. The lecture was conducted at the beginning of the socialization of abdimas activities. This activity was held from the end of July to the end of August 2021. There were 9 teachers who were participants in the implementation of these abdimas. Initial socialization is done through video conferences, and teachers are able to improve the content of draft articles that have been compiled. Assistance services during the period between socialization to submission, done using email (Gmail), Google Drive, and WhatsApp application. Discussions were conducted during the assistance activities of article preparation, and practice methods were used when teachers submitted in OJS Jurnal ARISEN (Nasional). Applications used in performing this abdimas include Zoom, Gmail, Google Drive, and WhatsApp (WAG). Abdimas activities carried out have hit the expected target.Permasalahan yang melatarbelakangi diadakannya abdimas ini adalah, kebutuhan peningkatan performance guru dalam kemampuan menulis karya ilmiah. Karya ilmiah guru sangat dibutuhkan untuk pemenuhan salah satu syarat peningkatan jabatan guru. Abdimas ini bertujuan untuk: memberikan pengetahuan kepada guru mengenai kaidah penulisan artikel ilmiah; memberikan layanan dan asistensi kepada guru, bagaimana melakukan pengembangan artikel dari laporan penelitian; membimbing guru dalam melakukan proses submit Artikel dalam jurnal nasional. Metode yang digunakan dalam abdimas ini ada beberapa jenis: ceramah, diskusi, dan praktek. Ceramah dilakukan pada awal sosialisasi kegiatan abdimas. Kegiatan ini dilaksanakan pada akhir juli sampai dengan akhir Agustus 2021.Terdapat 9 orang guru yang menjadi peserta dalam pelaksanaan abdimas ini. Sosialisasi awal dilakukan melalui vicon, guru mampu memperbaiki konten draf artikel yang telah disusun. Layanan Asistensi selama rentang waktu antara sosialisasi sampai dengan submitting, dilakukan menggunakan email (gmail), Google Drive dan aplikasi whatsapp. Diskusi dilakukan selama kegiatan pendampingan penyusunan artikel, dan metode praktek dipergunakan pada saat guru-guru melakukan submit di OJS Jurnal ARISEN (Nasional). Aplikasi yang dipergunakan dalam melakukan abdimas ini antara lain: Zoom, gmail, google drive, dan whatsapp (WAG). Kegiatan abdimas yang dilaksanakan telah mencapat target yang diharapkan.